Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1001/archneur.55.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Magnetic Resonance Imaging Findings in Machado-Joseph Disease

Abstract: Affected afferent and efferent cerebellar tracts and atrophy of the frontal and temporal lobes and globus pallidus are characteristics of MRI of patients with MJD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
93
1
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 14 publications
14
93
1
3
Order By: Relevance
“…These particularities may explain some of the differences we found 17 . In agreement to our data, reduced brainstem and cerebellar volume in MJD/ SCA3 patients has been widely demonstrated [9][10][11][12][13] . The most affected brain stem structure was the pons, with an average volume reduction of 35.7%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These particularities may explain some of the differences we found 17 . In agreement to our data, reduced brainstem and cerebellar volume in MJD/ SCA3 patients has been widely demonstrated [9][10][11][12][13] . The most affected brain stem structure was the pons, with an average volume reduction of 35.7%.…”
Section: Discussionsupporting
confidence: 93%
“…It is noteworthy that our measurements included part of the cerebellar peduncles and not only the ventral pons, since it is impossible to define the cerebellar anterior limit and brain stem anatomically. It has already been demonstrated that the volumes of the peduncles are decreased in the disease and that there is a positive correlation between the width of the cerebellar peduncle and the diameter of the pons 12 . The most affected vermis subdivisions were V1 and V2 (with an average reduction of 37%) whereas V3 was relatively spared with an average reduction of 24%.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, a study by Murata et al published in 1998 in which the authors used magnetic resonance imaging also showed the presence of pontocerebellar atrophy and atrophy of the globi pallidi and frontal and temporal lobes 2,3,26 .…”
Section: Sca 3 (Machado-joseph Disease)mentioning
confidence: 99%
“…The SCA types defined as SCA 4,5,11,13,14,15,18,19,20,21,22,23,25,26,27,28,29 and 30 represent very rare forms and have been diagnosed in a small number of cases in different parts of the world, some of which were only reported in isolated families.…”
Section: Scas -Very Rare Typesmentioning
confidence: 99%